THE STUDY OF THE MICROBIOTA OF THE NASOPHARYNX OF HEALTHY CHILDREN IN DIFFERENT AGE GROUPS BY GAS CHROMATOGRAPHY - Андриянова, Ирина Владимировна (Mother and Baby in Kuzbass, 2023)
We examined 84 healthy children aged 3 to 12 years using gas chromatography with mass spectrometry microbial markers. It was found that in addition to the cultivated part of the microbiota method reveals hard cultured microorganisms and thereby expand understanding of the colonization of the mucous membrane of the nasopharynx is normal.